Supply Chain Management on Inventory Indonesian Drug Industry - Firdaus Firdaus; Roos Kities Andadari; Hari Murti Mahatma Putra; Sri Sulandjari (Universitas Islam Sultan Agung, 2020)
The development of the human population in the world, especially Indonesia, to date is approximately 260 million people, making Indonesia in a big challenge where Indonesia must be able to meet the domestic drug supplies needed by the community. The availability of drugs is still an obstacle in the National Health Insurance in Indonesia, this requires the role of the pharmaceutical industry in supporting drug availability by implementing good supply chain management. The focus of this discussion is to look at drug supplies in Indonesia in meeting people's needs and identify factors for production planning, production capacity and raw material procurement for the pharmaceutical industry in supporting the availability of drugs to support the National Health Insurance. This research is a descriptive study by collecting information from various literatures on pharmacy and medicines in Indonesia with a focus on the discussion of production planning, production capacity and raw material procurement and delivery to pharmaceutical companies in supporting drug availability. Because the planning for drug needs used as a basis for drug procurement is inaccurate so that pharmaceutical companies cannot make accurate production plans and the quantity of drugs for the community is inaccurate, time and unavailable at any time, the need for and procurement of materials still depends on imported raw materials from abroad around 95% with a lead time of 1-3 months so that it has the potential to deplete drug supplies and make the National Health Insurance in Indonesia worse.